Exploring Hindering and Facilitating Mechanisms of Digital Awareness and the Role of Intra- and Interpersonal Factors via a Scoping Review of Research - Brummer, Leonie (Journal of Education and Learning Environments, 2025)
Our current society requires individuals to be sufficiently digitally literate, and these individuals can be labelled as digital citizens—(success)fully participating in and operating on different levels of our society, such as in public, work, and/or private lives. With our increasingly digitally mediated society, identifying hindering and facilitating mechanisms and intra- and interpersonal factors provides us insight into the influential factors to become digital aware and/or to increase the quality of the awareness—with subsequent consequences for society and education. Via a scoping review of the last nine years and covering 42 articles, these mechanisms and individual factors are reported on in existing research about digital literacy and digital citizenship—reasoning that these mechanisms and factors also influence digital awareness. Facilitating mechanisms and intrapersonal factors (e.g., skills, knowledge) were mentioned more often than hindering mechanisms (e.g., disengagement) and interpersonal factors (e.g., communication). Method sections included fewer factors than introductions, allowing for sufficient delimitation of research. Overall, there was a cognitive dominance of facilitators/hindrances and intrapersonal factors. Overlap exists between hindrances and facilitators; these can be considered two ends of a spectrum (e.g., disengagement and engagement). Furthermore, the interplay of hindrances and facilitators and intrapersonal factors calls for more research to reveal unique contributions of each factor.